Assessment and Optimization of Green Buildings in Inpatient Buildings Using EDGE Building Rating (Case Study: Graha Amarilis of Karsa Husada Batu Academic Hospital) - Angga Perdana; Agung Sedayu; Nur Kharismawardani; Krisna Adi Permana (Pusat Publikasi Nusantara, 2024)
The Graha Amarilis inpatient building has high Energy, Water, and material consumption because it operates 24 hours daily. The building’s performance must be evaluated based on green building standards to ensure the sustainability of the building and the environment surrounding it. This study aims to determine the performance of green buildings and optimize the Graha Amarilis inpatient building. A combined strategy of case studies with simulations is used as research methodology. Field surveys and measurements were carried out on research cases and digitally modeled using Autodesk REVIT. Then, building performance analysis calculations are carried out using the EDGE Building application simulation method, which presents data on green rating of Energy, Water, and Material saving in buildings. The results of this study were obtained on energy and water items that had not reached green building rating in EDGE Building by 20%. So, optimizing energy items at points EEM 18, EEM 07, and EEM 33 and Water at points WEM 01, WEM 02, WEM 14, and WEM 15 is necessary. Finally, after several simulations on that item, Energy saving consumption becomes 20.07 %, Water 34.69%, and Material 23.00%. With these adjustments, the Graha Amarilis inpatient Building can reach the green building standards and become more sustainable and environmentally friendly